Independence and its lexical expression in the Aurora de Chile - Franco Figueroa, Mariano (Boletín de Filología, 2010)
Based on the weekly newspaper Aurora de Chile, a linguisticanalysis is here introduced including both the description of lexicalcharacterizations as they adapted to the new sociolinguistic contexts inthe historical period of the colonial emancipation and the grammaticalphenomena that allow for the observation of differentiating features ofthe language being established in the Chilean society of the time. Onthe one hand, it is of interest to observe the lexical variation displayedin this journalistic text, which represents an illustrated ideology,in order to better understand the degree of penetration of the newpolitical and social vocabulary, with voices in many cases recreatedwith uses dominating the insurgent communities. On the other hand,the description of the grammatical phenomena and general vocabularyof this corpus provides concrete data regarding the preference of theselinguistic variants and the degree of standardization that they acquirein time, as emerging uses of the Spanish language in Chile, either asthe consolidation of traditional syntactic structures and vocabularyor as innovative mechanisms in the differential American grammarand vocabulary.